Egyenletek grafikus megoldása – 2.

(lineáris → abszolútérték, másodfokú, négyzetgyök)

1. |x – 1| – 2 = 1
M1(4; 1)M2(–2; 1)
2. |x + 5| – 4 = 0,5x + 1,5
M1(–7; –2)M2(1; 2)
3. |x |– 3 = 0,5x + 1,5
M1(–3; 0)M2(9; 6)
4. –|x – 2| + 5 = x/3 – 1
M1(–6; –3)M2(6; 1)
5. –|x + 1| + 6 = 5x/7 + 5
M1(–7; 0)M2(0; 5)
6. |x – 1| – 4 = x/3 – 1
M1(–1,5; –1,5)M2(6; 1)
7. |x + 1| – 4 = –x/3 + 1
M1(–9; 4)M2(3; 0)
8. |x + 6| + 2 = –x/2 + 2
M1(–4; 4)M2(–12; 8)
9. |x – 1| – 5 = x + 2
M1(–3; –1)(Egy közös pont van!!!)
10. |x – 1| – 1 = x/2 + 1
M1(–2/3; –2/3)M2(6; 4)
11. |x + 3| – 2 = x/2 + 1
M1(–4; –1)M2(0; 1)
12. –|x| + 4 = x/2 + 1
M1(–6; –2)M2(2; 2)
13. –|x| + 6 = x + 2
M1(2; 4)(Egy közös pont van!!!)
14. x + 2 = x2
M1(–1; 1)M2(2, 4)
15. (x – 4)2 – 3 = –2
M1(3; –2)M2(5; –2)
16. x2 – 3 = –x – 3
M1(0; –3)M2(–1; –2)
17. (x + 4)2 – 4 = x + 2
M1(–5; –3)M2(–2; 0)
18. – x/2 – 3 = (x – 1)2 – 11
M1(–2; –2)M2(3,5; –4,75)
19. –x2 + 3 = –x/2 – 2
M1(–2; –1)M2(2,5; –3,25)
20. – (x + 2)2 + 8 = x + 4
M1(–5; –1)M2(0; 4)
21. (x + 3)2 – 6 = –2x – 9
M1(–6; 3)M2(–2; –5)
22. – (x – 1)2 + 4 = x – 3
M1(–2; –5)M2(3; 0)
23. (x – 2)2 – 10 = –x – 2
M1(–1; –1)M2(4; –6)
24. (x – 1)2 – 6 = –2x – 1
M1(–2; 3)M2(2; –5)
25. (x + 1)2 – 2 = 2x + 3
M1(–2; –1)M2(2; 7)
26. |x| – 3 = x/3 + 1
M1(–3; 0)M2(6; 3)
27. x2 – 3 = –x – 3
M1(–3; 6)M2(2; 1)
28. (x – 2)2 – 7 = 2x – 3
M1(0; –3)M2(6; 9)
29. (x – 2)2 – 7 = 3x – 9
M1(1; –6)M2(6; 9)
30. |x – 2| – 7 = x/3 – 5
M1(0; –5)M2(6; –3)
31. |x + 3| – 6 = 3x/5 – 1
M1(–5; –4)M2(5; 2)
32. –|x + 3| + 6 = x + 3
M1(–6; –3)(Egy közös pont van!!!)
33. sqrt(x + 2) – 3 = –x – 3
M1(–1; –2)(Egy közös pont van!!!)
34. sqrt(x – 3) + 1 = –x/4 + 3
M1(12; 0)(Egy közös pont van!!!)
35. sqrt(x + 3) – 1 = x/3
M1(–3; –1)M2(6; 2)
36. -sqrt(x + 3) + 2 = –x – 1
M1(–3; 2)M2(–2; 1)
37. -sqrt(x + 5) = –x/4 – 2
M1(–4; –1)M2(4; –3)
38. sqrt(x + 4) + 1 = x/3 + 3
M1(–3; 2)M2(0; 3)
39. sqrt(x – 2) + 1 = x/3 + 1
M1(3; 2)M2(6; 3)
40. sqrt(x – 1) + 2 = x/4 + 1,75
M1(1; 2)M2(17; 6)